IMPACTOS POTENCIAIS DA NEGOCIAÇÃO DA ALCA SOBRE OS INVESTIMENTOS EXTERNOS EM SERVIÇOS PROFISSIONAIS NO BRASIL - Alexandre, Michel; Canuto, Otaviano; Lima, Gilberto Tadeu (Análise Econômica, 2009)
The paper deals with implications of hypothetical results of the negotiations on the Free Trade Area of the Americas on foreign direct investment in some professional services in Brazil. Based upon the presupposition of regulatory convergence/harmonization, whose center of gravity would be located in the most developed economies, it is discussed the extent to which the local environment for the national producers of those services would change with the possibility of greater presence of international competitors.